Komiczno-humorystyczny charakter wypowiedzi w dramatach Olega Bogajewa - Juchniewicz, Agnieszka (Studia Rossica Posnaniensia, 2022)
The aim of this paper is, first of all, to discuss the linguistic sphere in Oleg Bogayev’s comedy works. We would like to pay special attention to the way the characters express themselves. The way Bogayev’s characters create reality is deeply rooted in the spirit of postmodernism, which is reflected primarily in the playwright’s bold experimentation with words, especially in the area of constructed replicas. Language saturated with humour and comical elements can be found in the plays Maria’s field (2004) and Notes of a prosecutor in love (2019). In each of these works, the mode of expression is shaped slightly differently, primarily because of the relationship between the word and the reality presented. They have been constructed according to different genre patterns. The comical and humorous character is most clearly manifested in the former at the linguistic level, while in the latter it is conditioned by the situation. On the one hand, there is humour in Bogayev’s works that can be described as good-natured and comical, directed at human existence and social problems, both as perceived by the author and the characters. On the other hand, there is satirical humour that destabilises the image of the presented world, shattering stereotypes and fixed beliefs. Humour often lurks the tragedy and absurdity of the human world, with all its weaknesses and problems.